First Detection of mcr-9 in a Multidrug-Resistant Escherichia coli of Animal Origin in Italy Is Not Related to Colistin Usage on a Pig Farm - Flavia Guarneri; Cristina Bertasio; Claudia Romeo; Nicoletta Formenti; Federico Scali; Giovanni Parisio; Sabrina Canziani; Chiara Boifava; Federica Guadagno; Maria Beatrice Boniotti; Giovanni Loris Alborali (MDPI AG, 2023)
The emergence of colistin resistance raises growing concerns because of its use as a last-resort antimicrobial for the treatment of severe gram-negative bacterial infections in humans. Plasmid-borne mobile colistin resistance genes (mcr) are particularly worrisome due to their high propensity to spread. An mcr-9-positive Escherichia coli was isolated from a piglet in Italy, representing the first isolation of this gene from an E. coli of animal origin in the country. Whole genome sequencing (WGS) revealed that mcr-9 was borne by an IncHI2 plasmid carrying several other resistance genes. The strain was indeed phenotypically resistant to six different antimicrobial classes, including 3rd and 4th generation cephalosporins. Despite the presence of mcr-9, the isolate was susceptible to colistin, probably because of a genetic background unfavourable to mcr-9 expression. The lack of colistin resistance, coupled with the fact that the farm of origin had not used colistin in years, suggests that mcr-9 in such a multidrug-resistant strain can be maintained thanks to the co-selection of neighbouring resistance genes, following usage of different antimicrobials. Our findings highlight how a comprehensive approach, integrating phenotypical testing, targeted PCR, WGS-based techniques, and information on antimicrobial usage is crucial to shed light on antimicrobial resistance.